THE SECONDARY STRUCTURE OF THE FRICTION SURFACE OF THE CONTACT WIRE - Aulin, O. V.; Baranovskyi, D. M.; Kuznetsov, V. H. (Science and Transport Progress, 2005)
The process of secondary structures formation on the friction surface of contact wire in the process of operation has been explored. A possibility of obtaining and modifying secondary material structures within the system «contact wire – current collection material» by means of laser technologies has been displayed. It has been established that in the laser irradiation area of the material reductive-oxidative interactions of carbon dioxide with copper as well as intensive diffusive processes of carbon into the copper matrix occur.